ADOLESCENCE AND USE OF PSYCHOACTIVE SUBSTANCES: A ESCAPE FROM REALITY MECHANISM (CIPEEX, 2022)
OBJECTIVE: THE OBJECTIVE OF THIS STUDY WAS TO HIGHLIGHT THE FACTORS THAT INFLUENCE THE DEPENDENCE OF PSYCHOACTIVE SUBSTANCES AND THE CONNECTION WITH THE CONFLICTS THAT MARK THE PHASE OF ADOLESCENCE SUCH AS; CONFLICTING FAMILY RELATIONSHIPS, THE INFLUENCE OF THE MEDIA ON DRUG USE AND PHYSICAL, EMOTIONAL AND SOCIAL SUFFERING. MATERIALS AND METHODS: THIS IS AN EXPLORATORY DESCRIPTIVE STUDY WITH A QUALITATIVE FOCUS ON THE FACTORS THAT INFLUENCE PSYCHOACTIVE SUBSTANCES IN ADOLESCENCE AS AN OBJECT OF STUDY. THE RESEARCH WAS CARRIED OUT IN A PRIVATE EDUCATIONAL INSTITUTION IN THE INTERIOR OF THE STATE OF GOIS. FOR DATA COLLECTION, OBSERVATION METHODS AND QUESTIONNAIRE APPLICATION WERE USED, DATA APPRECIATION WAS MADE THROUGH CONTENT ANALYSIS. FURTHERMORE, THE STUDY COLLECTED INFORMATION ABOUT THE GUARDIANSHIP OF THE ADOLESCENTS INTERVIEWED, REGARDING FAMILY SUPPORT AND THE SOCIAL ENVIRONMENT TO WHICH THEY BELONG. THIS STUDY WAS THE RESULT OF AN ACTIVITY PROPOSED IN THE DISCIPLINE OF NURSING FOR THE HEALTH OF YOUNG PEOPLE AND ADOLESCENTS, WHICH COMPOSES THE CURRICULAR STRUCTURE OF THE NURSING COURSE AT FACULDADE EVANGÉLICA DE CERES. RESULTS AND DISCUSSION: TWENTY 16-YEAR-OLD ADOLESCENTS PARTICIPATED IN THIS STUDY. FROM THE RESULTS OBTAINED, IT WAS OBSERVED THAT 50% OF ADOLESCENTS FACE SOCIAL, MENTAL AND SPIRITUAL DIFFICULTIES. PARTICIPANTS CLAIMED TO EXPERIENCE THEIR OWN ANGUISH, DISORDERS AND ADVERSITIES ALONE, AS THEY DO NOT FEEL CONFIDENT IN SHARING THEIR FEELINGS, AND THEREFORE, AS AN ATTEMPT TO ESCAPE, THEY ABUSE PSYCHOACTIVE SUBSTANCES (SPA'S), ESPECIALLY CENTRAL NERVOUS SYSTEM DEPRESSANTS, MORPHINE, HEROIN AND ALCOHOL. FURTHERMORE, A QUARTER OF THE YOUNG PARTICIPANTS USE SPAS BECAUSE THEY ARE IN A STATE OF DEPRESSION, 25% USE THEM FOR DIFFERENT REASONS AND THE INFLUENCE OF FRIENDS. WITH REGARD TO FREQUENCY, IT WAS FOUND THAT THE USE OF SPA'S IS FREQUENT, AND USUALLY WEEKLY. CONCLUSION: HE EMPHASIZES THAT IT IS OF PARAMOUNT IMPORTANCE THAT THIS TOPIC IS DEEPENED AND THAT THERE ARE HEALTH PROGRAMS IN PARTNERSHIP WITH EDUCATION WITH THE PRINCIPLE OF PREVENTING, MONITORING AND, IF NECESSARY, TREATING YOUNG PEOPLE AND ADOLESCENTS WHO USE PSYCHOACTIVE SUBSTANCES.
Keywords: adolescente; drogas; substÃ¢ncias psicoativas; vulnerabilidade; transtornos